Effect of Pre-treatment and Processing on Nutritional Composition of Cassava Roots, Millet, and Cowpea Leaves Flours - Onyango, Samwel Ochieng; Abong, George Ooko; Okoth, Michael Wandayi; Kilalo, Dora C.; Mwang'ombe, Agnes Wakesho (Frontiers in Sustainable Food Systems, 2021)
Cassava roots, millet and cowpea leaves have short storage life thus the need for simple post-harvest handling and storage protocol to ensure prolonged availability to fully contribute toward food and nutrition security, a major challenge within Sub-Saharan Africa. The current study sought to investigate the effect of pre-treatment and processing on cyanide safety and nutrition composition of cassava roots, millet and cowpea leaves flours. The study used three popular cassava varieties grown along the Kenyan coast, cowpea leaves (M66) grown as vegetable and pearl millet. The study used analytical techniques as guided by AOAC standard methods, to determine the nutritional composition of the individual crops while subjecting them to pre-treatment processes (blanching, peeling, washing, drying, and fermentation) and optimizing for maximum nutrient composition. The cyanide content ranged 7.8–9.5, 3.4–5.0, and 2.2–2.8 ppb for raw, untreated, and fermented cassava flours, respectively. The carbohydrates content was in the range of 35–37, 81.73–83.49, and 70.28–71.20% for raw cowpea leaves, cassava roots, and millet, respectively; the carbohydrate content for untreated flours was in the range of 35.68–35.19, 66.07–83.49, and 66.07–68.89% for cowpea leaves, cassava roots, and millet, respectively; the carbohydrate content for the fermented flours was in the range of 29.06–28.01, 79.68–84.36, and 69.08–70.12% for cowpea leaves, cassava roots, and millet, respectively. The protein content was in the range of 25.69–26.01, 1.2–18, and 11.1–13.3% for untreated cowpea, cassava, and millet flours, respectively; fermented flours protein content was in the range of 25.7–29.3, 1.3–2.2, and 8.5–11.1% cowpea, cassava, and millet flours, respectively. Iron and zinc contents were in the range of 4.31–9.04, 1.0–1.3; 7.98–7.89, 1.21–1.25; 6.58–8.23, 0.99–1.22 (mg/100 g dwb) for raw, untreated, and fermented cowpea flours, respectively. Pre-treatment had significant effects (P ≤ 0.05) on cyanide content and nutritional composition of each of the flours. Farmers should be trained to utilize such simple processing techniques.